Prognostic factors and nomogram for pulmonary resected high-grade neuroendocrine carcinomas: a 20-year single institutional real-world experience - Lei Liu; Jiaqi Zhang; Ke Zhao; Chao Guo; Cheng Huang; Shanqing Li; Yeye Chen (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Pulmonary high-grade neuroendocrine carcinomas(pHGNEC) encompassing small cell lung cancer (SCLC) and large cell neuroendocrine carcinoma (LCNEC) are clinically aggressive tumors with poor prognosis. The role of surgery and prognostic factors guiding management remain unclear. We aimed to analyze prognosis following resection and identify predictive variables. Methods This retrospective study analyzed 259 patients undergoing pHGNEC resection from 2001–2023. Overall survival (OS) and disease-free survival (DFS) were evaluated using Kaplan–Meier curves. Prognostic factors were assessed with Cox regression and visualized using nomogram tools. Results Minimally invasive surgery was associated with better OS (p = 0.001) and DFS (p = 0.001). Higher T stage predicted worse OS (T2 p = 0.044, T4 p = 0.007) and DFS (T2 p = 0.020, T4 p = 0.004). Advanced TNM stage III (OS p = 0.018; DFS p = 0.015) and IV (OS p < 0.001; DFS p < 0.001) also correlated with poorer prognosis. In the SCLC subgroup, elevated preoperative CEA independently predicted worse OS (p = 0.012) and DFS (p = 0.004). T4 disease (OS p < 0.001; DFS p = 0.002) and advanced TNM staging (stage III OS p = 0.043; DFS p = 0.045; stage IV OS p < 0.001, DFS p < 0.001) were associated with worse outcomes. In LCNEC patients, VATS resection improved OS (p = 0.048) and DFS (p = 0.027) despite conversion. Prior malignancy predicted worse OS (p < 0.001). Advanced TNM disease (stage III OS p = 0.047; stage IV OS p = 0.003, DFS p = 0.005) were also negative prognostic factors. The prognostic nomogram incorporating above variables effectively stratified risk. Calibration plots revealed good correlation between predicted and actual survival. Conclusions We identified minimally invasive surgery, early TNM stage, younger age, and normal preoperative CEA as positive prognostic factors following pHGNEC resection. Our study provides an applicable prognostic nomogram to facilitate personalized pHGNEC management.